2018
DOI: 10.1111/ajt.14719
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the new kidney allocation system A2/A2B → B policy on access to transplantation among minority candidates

Abstract: Blood group B candidates, many of whom represent ethnic minorities, have historically had diminished access to deceased donor kidney transplantation (DDKT). The new national kidney allocation system (KAS) preferentially allocates blood group A2/A2B deceased donor kidneys to B recipients to address this ethnic and blood group disparity. No study has yet examined the impact of KAS on A2 incompatible (A2i) DDKT for blood group B recipients overall or among minorities. A case-control study of adult blood group B D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 15 publications
0
31
0
1
Order By: Relevance
“…The use of A2 to O or B recipients has been permissible and recommended for some time, resulting in a reduction in waiting times and comparable graft outcomes to conventional compatible transplantation . Initially, the number of participating centres participating was low , however, the new Kidney Allocation Scheme in the USA has led to a significant increase in A2 donors being used for ABO‐incompatible transplants . Additionally, there is mounting evidence that for patients with low‐titres of anti‐A or anti‐B antibody (<1:16), there is no requirement for any augmentation to conventional immunosuppression, or need for desensitization therapy with plasmapheresis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of A2 to O or B recipients has been permissible and recommended for some time, resulting in a reduction in waiting times and comparable graft outcomes to conventional compatible transplantation . Initially, the number of participating centres participating was low , however, the new Kidney Allocation Scheme in the USA has led to a significant increase in A2 donors being used for ABO‐incompatible transplants . Additionally, there is mounting evidence that for patients with low‐titres of anti‐A or anti‐B antibody (<1:16), there is no requirement for any augmentation to conventional immunosuppression, or need for desensitization therapy with plasmapheresis .…”
Section: Discussionmentioning
confidence: 99%
“…However, clinical exploitation of this phenomenon has been limited ‐ in a retrospective analysis of A2 kidney use in the USA, it was found that only 15% of the possible A2 allografts had been allocated to O or B recipients . Nonetheless, the recent changes in the US Kidney Allocation Scheme (KAS) allow A2 to B or O allocation and demonstrate improved rates of transplantation for Blood Group B recipients, albeit with little of the predicted effect on rates of transplantation for ethnic minorities . Centres for liver and infant heart transplantation, by necessity because of organ shortage, have developed a practice of ddABOi transplantation .…”
Section: Introductionmentioning
confidence: 99%
“…While the transplant rate for younger recipients increased, it fell modestly for those aged ≥65 years (who would benefit most from early transplantation). No increase in transplant rates for blood group B recipients was observed due to the low uptake of A 2 and A 2 B kidneys, especially in ethnic minorities for which this initiative was targeted . There was also a marginal increase in the non‐utilization rate.…”
Section: Case Study: Changes To the Kidney Allocation System In The Usmentioning
confidence: 96%
“…Though subtype-compatible transplants have increased sharply with KAS ( Figure 5), the provision for transplanting A 2 or A 2 B kidneys into compatible blood type B candidates, who are still biologically disadvantaged due to relatively few donors having blood type B [3,40], remains underutilized [42,43]. Though an OPTN study found blood type to be the candidate characteristic third-most associated with disparities in transplant access, the factor most associated with disparities is geography, most notably the DSA of a candidate's transplant program [40,44].…”
Section: Improving Equity In Access To Kidneysmentioning
confidence: 99%